Electron Capture in Nuclear Structure and Astrophysics - Giannaka, P.; Kosmas, T. S.; Tsakstara, V. (HNPS Advances in Nuclear Physics, 2019)
Electron capture on nucleons and nuclei, is one of the most important weak interaction processes in the dynamics and evolution of massive stars. Especially on nuclei of the Fe mass region the role of e− capture is crucial in the phase of stellar core collapse. Furthermore, a realistic treatment of electron capture on heavy nuclei provides signi cant information in the hydrodynamics of core collapse and bounce. In this work, we exploit the advantages of a recently published numerical approach to perform nuclear structure calculations of the electron capture in F e group nuclear isotopes. As a rst concrete example, which is simultaneously o ering a good test of ourmethod,wechoosethereaction56Fe(e−,νe)56Mn* that plays a decisive role in core collapse supernovae. We also improve the previous formalism by constructing compact analytical expressions for the required reduced matrix elements of all basic multipole operators in isospin representation. Such a compact formalism o ers the advantage of performing state-by-state calculations of the transition rates for semi- leptonic nuclear processes through advantageous computer codes written in isospin representation.